Effect of Hydrolyzing Agents on the Properties of Poly (Ethylene Glycol)-Fe3O4 Nanocomposite - Karaoǧlu, E.; Kavas, H.; Baykal, A.; Toprak, M. S.; Sözeri, H. (Nano-Micro Letters, 2011)
A PEG assisted hydrothermal route was used to study the influence of the hydrolyzing agent on the properties of PEG-iron oxide (Fe3O4) nanocomposites. Iron oxide nanoparticles (NPs), which confirmed by X-ray diffraction analysis, were successfully synthesized by a hydrothermal method in which NaOH and NH3 were used as hydrolyzing agents. Formation of PEG-Fe3O4 nanocomposite was confirmed by Fourier transform infrared spectroscopy (FTIR). Samples exhibit different crystallite sizes, which estimated based on line profile fitting as 10 nm for NH3 and 8 nm for NaOH hydrolyzed samples. The average particle sizes obtained from transmission electron microscopy was respectively 174±3 nm for NaOH and 165±4 nm for NH3 gas hydrolyzed samples. Magnetic characterization results reveal superparamagnetic characters despite a large particle size, which may indicate the absence of coupling between the nanocrystals due to the polymer in the nanocomposite. The conductivity curve demonstrates that sDC strongly depends on the temperature.